Taking on the challenge: small, micro and medium enterprises (SMMEs) and socioeconomic development in South Africa. - Tendai Makwara (DBA Candidate) (African Journal of Hospitality, Tourism and Leisure, 2019)
This theoretical study investigated small, micro and medium enterprises (SMMEs) impact on development in South Africa. The aim of the study was to assess the current role of small micro and medium enterprises (SMMEs) in spearheading economic growth and addressing social problems in an environment where large business and government are seemingly doing very little. Thus the study analyses SMME roles towards addressing challenges of unemployment and chronic social ills of poverty, inequality and social exclusion in the country. This study followed a desktop literature review research design to gather data on negative actions by government and large business that accentuate social problems faced by communities and retard socioeconomic development, as well as the individual roles SMMEs fulfil to meet socioeconomic development objectives. Research findings show SMMEs are at the forefront of job creation and building the social and political equity in the country among other development outcomes. As a theoretical study, this paper provides no empirical evidence to validate the conclusions and observations, thus future empirical research that account and assess the value of SMMEs contributions to the creation of economic, social and political equity in the country are recommended.